Assessing School Readiness in the Preschool-to-Primary Transition: A Systematic Review - Subhan Subhan (Pedagogik Journal of Islamic Elementary School, 2025)
Despite growing global recognition of the pivotal role that the preschool-to-primary transition plays in children's long-term academic and social trajectories, the multi-dimensional nature of school readiness remains insufficiently synthesized across diverse educational contexts. This study aimed to systematically assess the indicators of school readiness during the preschool-to-primary school transition and to identify the ecological, socio-emotional, cognitive, and institutional factors that collectively determine transition quality. A systematic review methodology guided by the PRISMA 2020 framework was employed, drawing on searches across five major databases Scopus, Web of Science, ERIC, PsycINFO, and Google Scholar—covering publications from 2015 to 2024; following two-stage screening and quality appraisal using the Mixed Methods Appraisal Tool and Cohen's kappa inter-rater reliability (κ = 0.84), 35 peer-reviewed studies from 17 countries were retained for narrative synthesis supplemented by meta-analytic sub-synthesis where methodological homogeneity permitted. Findings revealed that school readiness is a multi-dimensional construct in which executive function and socio-emotional regulation consistently produced larger effect sizes (d = 0.38–0.82) than conventional academic skill measures, while parental involvement, family-school connectivity, and cross-institutional teacher collaboration emerged as significant ecological predictors of transition quality independent of child-level characteristics. Future research should prioritize longitudinal multi-wave designs spanning the full preschool-to-primary arc, intervention studies evaluating cross-institutional professional development programs, and contextually grounded investigations within Indonesian and Southeast Asian settings where the empirical evidence base remains critically underdeveloped.